2019
DOI: 10.1002/jhet.3622
|View full text |Cite
|
Sign up to set email alerts
|

Design, Regiospecific Green Synthesis, Chemical Computational Analysis, and Antimicrobial Evaluation of Novel Phthalazine Heterocycles

Abstract: Phthalazines have received considerable attention for their wide antimicrobial activity. Regiospecific nucleophilic attack of 4‐benzylphthalazin‐1‐ol by the 1‐oxo rather than the aza group on different alkyl halides gave novel phthalazine heterocyclic derivatives. Moreover, a variety of nucleosides bonded to electron‐withdrawing groups were synthesized using 4‐benzylphthalazine‐1‐ol. The density functional theory has been used to investigate the electronic structure of the synthesized compounds. All of the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Chlorohydrins and ECH were used to prepare derivatives of pyridine [139][140][141], phtalazines [142][143][144], oxazolidinone [122,145,146], triazinones [147], thioglycoside [148] and aziridines [149]. N-Heterocycles have wide applicability as antibiotics [150][151][152].…”
Section: Funcionalization Of Aza-heterocyclic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chlorohydrins and ECH were used to prepare derivatives of pyridine [139][140][141], phtalazines [142][143][144], oxazolidinone [122,145,146], triazinones [147], thioglycoside [148] and aziridines [149]. N-Heterocycles have wide applicability as antibiotics [150][151][152].…”
Section: Funcionalization Of Aza-heterocyclic Compoundsmentioning
confidence: 99%
“…The reaction of 1,3-DCH and ECH with arylphthalazinone yielded phthalazin derivatives [142][143][144]147]. Figure 18a shows the N-alkyl products resulting from the nucleophilic attack of the nitrogen in the phthalazinone on 1,3-DCH (33% to 36% yield) or ECH (51% to 54% yield).…”
Section: Synthesis Of Pthalazine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in terms of this aspect, many studies have been focused on pyridazin-(3H)-ones, which are characterized to possess good analgesic and antiinflammatory activities. Besidespyridazinones, these studies have indicated that the heterocyclic ring substitutions at the six position, and the presence of acetamide side chain when linked to the lactam nitrogen of pyridazinone ring at the two position of the pyridazinone ring, improve the analgesic and antiflammatory activity along with nil or very low ulcerogenicity [27][28][29][30] . In view of the aforementioned facts, it seemed most interesting to synthesize some [4-((3-chloro-4methylphenyl)-2-substituted phthalazin-1(2H)one] derivatives with the aim to obtain more precise information about the course of reactions and biological activities.…”
Section: Introductionmentioning
confidence: 99%